PERMODELAN POLA PERENCANAAN KEUANGAN BERDASARKAN STATUS PERNIKAHAN - Hakim, Lukmanul; Andriani, Sri; Umami, Nenny Noor (PATTIMURA UNIVERSITY, 2021)
A Marital status at community can make an impact on financial management. The purpose of this study was to analyze financial planning based on marital status with the variables of financial attitude, financial behavior, and financial literacy towards people who live in Sumbawa. The data were analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS) through smartPLS version 3.0 software. The results of the analysis in this study indicate that (1) financial attitude has a significant effect on financial behavior both based on married and unmarried status, (2) financial attitude has a significant effect on financial literacy both based on married and unmarried status, (3) financial attitude has an effect significant on financial planning based on both married and unmarried status, (4) financial behavior has no significant effect on financial literacy both based on married and unmarried status, (5) financial behavior has no significant effect on financial planning both based on married and unmarried status, (6) financial literacy has no significant effect on financial planning based on both married and unmarried status, and (7) There is no difference in financial planning based on marital status